Simultaneous electrochemical detection of aspirin, ibuprofen and indomethacin using cobalt tetra amino phenoxy phthalocyanine nanoparticles and nitrogen doped carbon nanodots modified electrode - Dondo, Nyaradzai (Midlands State University, 2018)
Carbon nanodots (CNDs), nitrogen doped carbon nanodots (n-CNDs) and their composites with cobalt tetra aminophenoxy phthalocyanine nanoparticles (CoTAPhPcNPs) were employed towards the simultaneous detection of aspirin (ASA), ibuprofen (IBU) and indomethacin (INDO). The nanomaterials were characterized by FTIR, UV-Vis, TEM, cyclic voltammetry, electrochemical impedance spectroscopy, linear sweep voltammetry, chronoamperometry and differential pulse voltammetry. CoTAPhPcNPs/n-CNDs-GCE showed excellent electrooxidation of ASA, IBU and INDO and oxidation overpotentials were lowered. Higher surface coverages were observed indicating that modifiers were lying flat on the surface of the electrode. The CoTAPhPcNPs/n-CNDs-GCE gave catalytic rate constants of 1.655 x 101 M-1s-1, 1.42 x 101 M- 1s-1 and1.91 M-1s-1 for ASA, IBU and INDO respectively. The detection limits observed for ASA, IBU and INDO were 9.66 × 10-7, 4.19 ×10-7 and 7.2 × 10-7 M respectively. The adsorption equilibrium constants for ASA, IBU and INDO were found to be 1.05 x 105 M-1, 1.2 x 105 M-1 and 5.56 x 105 M-1 respectively. Furthermore, high Tafel slopes were observed indicating adsorption of each analyte to the surface of the electrode. The Gibb’s free energy for ASA, IBU and INDO were found to be -28.63 kJ mol-1, -28.96 kJ mol-1 and -27.07kJ mol-1 respectively. The developed sensor exhibited an excellent anti-interference property and good reproducibility towards the detection of ASA, IBU and INDO.